Navigating Legal Awareness in the Digital Era: Cultivating A Digital Culture in Indonesia - Hafizhah, Annisa (Mahadi: Indonesia Journal of Law, 2024)
This research investigates the various impacts of digital transformation on legal culture and societal norms in present-day Indonesia. By examining the convergence of legal changes, technological progress, and cultural shifts, the study underscores the significance of maintaining traditional values in the face of rapid digital advancements. Emphasizing the importance of legal literacy, the paper advocates for innovative educational initiatives, such as those utilizing film and podcasts, to improve public comprehension of legal concepts. The analysis highlights the careful equilibrium needed for Indonesia to embrace digital culture while preserving its diverse cultural legacy.